Biomarkers towards Ovarian Cancer Diagnostics: Present and Future Prospects - Meenal Rastogi; Sameer Gupta; Manisha Sachan (Brazilian Archives of Biology and Technology)
ABSTRACT Ovarian carcinoma accounts for highest mortality of all gynecologic malignancies as the disease is asymptomatic until late stages. Biomarkers such as CA-125 and HE4 are being currently used for diagnosis of ovarian cancer, but they show contradicting diagnostic accuracy. Therefore other biomarkers have been investigated for early detection of this disease, but no success has been obtained and no test has yet been recommended for screening a general population. In this instance, aptamers can be effectively used to identify tumor-specific antigens for early diagnosis and targeted therapy of ovarian cancer. This article provides an overview of the biomarkers/panels being explored as well as the potential of aptamers to improve current long-term survival rates of ovarian cancer.